Factors that Influence Consumers Purchase Intention in Buying Over the Counter Drug Online - Chiquita Purnomo; Pauline H Pattryanie Tan (Institute of Computer Science (IOCS), 2021)
The use and development of the online internet in all areas of activity has become part of people's habits, a behavior that allows people to adapt and find new solutions for market players, especially in the pharmaceutical sector in carrying out their sales activities online. Over the counter drug market growth especially in online channel. The purpose of this research was to determine the factors that influence consumer purchase intention in buying over the counter drug online. Technology Acceptances Model (TAM) and Virtual Experiential Marketing (VEM) as exogenous variable, trust as mediating variable and purchase intention as endogen variable. The study were analyzed using the Smart PLS- Structural Equation Model (SEM) third edition and it was conducted with electronic questionnaires using purposive sampling technique to consumers who purchased over the counter drug online in the last 6 months. The number of respondents in this study was 174 respondents. The results found that Technology Acceptances Model (TAM) and Virtual Experiential Marketing (VEM) variables had a positive effect on trust. Trust can mediate Technology Acceptances Model (TAM) with purchase intention and trust can mediate Virtual Experiential Marketing (VEM) with purchase intention. Furthermore, Technology Acceptances Model, Virtual Experiential Marketing and trust have a positive effect on purchase intention.